Kingdom of Moab: Political and cultural study through Mesha Inscription - Amer Aboud, Omar (Al-Adab Journal, 2019)
In the middle of the second millennium BC, the ancient Near East witnessed an economic, political and military struggle against ancient Syria (the Levant) among the existing empires, especially the Assyrian, Egyptian and the Atheist, to control the main trade route and economic and military domination. Their political system from tribal to property and even the demise of their kingdom in 583 BC. The cultural side of the religious faith of the gods and rituals, as well as the language of the Almabib and written records, which contained abundant information about them and their economic relations, Political and military relations with neighboring countries.